2012
DOI: 10.1038/tp.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Selective overexpression of Comt in prefrontal cortex rescues schizophrenia-like phenotypes in a mouse model of 22q11 deletion syndrome

Abstract: The 22q11.2 microdeletion is one of the highest genetic risk factors for schizophrenia. It is not well understood which interactions of deleted genes in 22q11.2 regions are responsible for the pathogenesis of schizophrenia, but catechol-O-methytransferase (COMT) is among the candidates. Df1/+ mice are 22q11.2 deletion syndrome (22q11DS) model mice with a hemizygous deletion of 18 genes in the 22q11-related region. Df1/+ mice showed enhanced response to the dopamine D1 agonist, SKF38393, and the N-methyl-D-aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 55 publications
4
16
0
1
Order By: Relevance
“…Similar to the Df1/+ mouse, 34 we found that Df(h22q11)/+ mice displayed increased locomotor activity in response to the NMDAr antagonists PCP and ketamine. Interestingly, the effect was age-dependent and only was observed after puberty (9-but not 7-week-old animals).…”
Section: Discussionmentioning
confidence: 50%
“…Similar to the Df1/+ mouse, 34 we found that Df(h22q11)/+ mice displayed increased locomotor activity in response to the NMDAr antagonists PCP and ketamine. Interestingly, the effect was age-dependent and only was observed after puberty (9-but not 7-week-old animals).…”
Section: Discussionmentioning
confidence: 50%
“…Its gene has several polymorphisms: Val/Val homozygotes have a PFC enzyme activity 40% higher than Met/Met homozygotes, therefore have lower dopamine levels in this region (Chen et al, 2004). The most common polymorphism, a Met substitution at codon 158, reduces the activity of COMT enzyme to one-quarter, resulting in a higher dopamine level in PFC (Kimoto et al, 2012;Lachman et al, 1996). Val(158)Met polymorphism (also known as rs4680) has therefore been considered a cognitive function modulator (Bearden et al, 2004;Farrell, Tunbridge, Braeutigam, & Harrison, 2012).…”
Section: S Oc I Al Cog Ni Ti On R El a Ti Onsh I P S Wi Th Sp E Ci mentioning
confidence: 99%
“…Schizophrenia-relevant sensory and psychomotor behaviors have been reported as disrupted in several of these models. The Df(16)A +/− mouse model has been shown to display baseline hyperactivity and an anxiogenic phenotype ( Stark et al 2008 ) while increased hyperactivity in response to MK-801 was reported in the Df/+ model ( Kimoto et al 2012 ). Similar to human carriers ( Sobin et al 2005 ) the Df(16)A +/− , Df1/+ and LgDel models displayed reduced prepulse inhibition ( Paylor et al 2001 ; Long et al 2006 ; Stark et al 2008 ) while the Df1/+ mutant had a increased acoustic startle response ( Paylor et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%